Free‐standing and flexible nano‐ZnO/PVDF composite thin films: impedance spectroscopic studies†. (13th May 2015) - Bhunia, Ritamay; Ghosh, Barun; Ghosh, Dibyendu; Hussain, Shamima; Bhar, Radhaballabh; Pal, Arun Kumar
<x xml:space="preserve">Abstract</x> Nanocrystalline ZnO‐impregnated polyvinylidene fluoride (nano‐ZnO/PVDF) composite films were prepared by sol‐gel technique. Free‐standing and flexible films with different nano‐ZnO loadings were synthesized. Addition of ZnO in PVDF host matrix modulated the impedance and dielectric properties. The composite films thus obtained were characterized by microstructural, XPS, and impedance spectroscopic measurements. Copyright © 2015 John Wiley & Sons, Ltd.